Use of Smartphone and GIS Technology for Sustainable Forestry in Eastern Ontario - Kennedy, Richard R. (Université d'Ottawa / University of Ottawa, 2012)
This study examined whether the current generation of consumer-grade digital mobile computing technology, so called smartphone technology, is usable to perform and improve field data collection in the context of sustainable forest management. An electronic data acquisition system, based on a handheld smartphone device and desktop geographic information system (GIS), was developed. A proprietary timber cruise application and commercial mapping software were used with the smartphone/desktop GIS to record and process forest stand and geospatial data. Usability testing was carried out to measure workflow efficiency and system performance of the smartphone GIS compared to traditional paper-based methods. The smartphone GIS successfully met performance objectives and significantly increased workflow efficiencies by improving data transfer and processing times over conventional paper methods; however, use of the mobile device resulted in greater data entry errors, increased data collection times, and led to more equipment malfunctions than use of paper recording methods together with a GPS and digital camera. Overall, the prototype electronic data acquisition system was not reliable as a stand-alone solution solely responsible for collecting cruise data, but was found to be well suited for ad-hoc mapping of forest features.
Keywords: Mobile GIS; Smartphone; Forestry; Ontario